WOMEN AND THEIR ROLE IN NATURAL RESOURCES: A STUDY IN WESTERN HIMALAYAS - Singh, Kiran (International Journal of Research -GRANTHAALAYAH, 2015)
Women roles in Himalayas put women in direct contact with natural resources such as forests, water, land and wildlife. They utilize and conserve these resources to supply basic needs for their families. Therefore conservation of natural resources in rural areas cannot be done without the involvement and training of women. They need to be educated on the values, management and sustainability of natural resources as alternative sources of livelihood. But to have success, they must only be appreciated as invisible land managers, but must benefit from relevant incentives in their cultural roles. This paper examines the roles of women in natural resource conservation, since their traditional activities bring them into daily interaction with natural resources, their impacts, attitudes and belief on the management, exploitation and sustainability of natural resource is critical for resource use and sustainability.